Lung transplantation for idiopathic pulmonary arterial hypertension on intraoperative and postoperatively prolonged extracorporeal membrane oxygenation provides optimally controlled reperfusion and excellent outcome. (27th July 2017) - Moser, Bernhard; Jaksch, Peter; Taghavi, Shahrokh; Muraközy, Gabriella; Lang, Georg; Hager, Helmut; Krenn, Claus; Roth, Georg; Faybik, Peter; Bacher, Andreas; Aigner, Clemens; Matilla, José R; et al.
Abstract: OBJECTIVES: Lung transplantation for idiopathic pulmonary arterial hypertension has the highest reported postoperative mortality of all indications. Reasons lie in the complexity of treatment of these patients and the frequent occurrence of postoperative left ventricular failure. Transplantation on intraoperative extracorporeal membrane oxygenation support instead of cardiopulmonary bypass and even more the prolongation of extracorporeal membrane oxygenation into the postoperative period helps to overcome these problems. We reviewed our experience with this concept. METHODS: All patients undergoing bilateral lung transplantation for idiopathic pulmonary arterial hypertension on intraoperative extracorporeal membrane oxygenation with or without prophylactic extracorporeal membrane oxygenation prolongation into the postoperative period between January 2000 and December 2014 were retrospectively analysed. RESULTS: Forty-one patients entered the study. Venoarterial extracorporeal membrane oxygenation support was prolonged into the postoperative period for a median of 2.5 days (range 1–40). Ninety-day, 1-, 3- and 5-year survival rates for the patient collective were 92.7%, 90.2%, 87.4% and 87.4%, respectively. When compared with 31 patients with idiopathic pulmonary arterial hypertension transplanted in the same period of time without prolongation of extracorporeal membrane oxygenation into the postoperative period, the results compared favourably (83.9%, 77.4%, 77.4%, and 77.4%; P  = 0.189). Furthermore, these results are among the best results ever reported for this particularly difficult patient population. CONCLUSIONS: Bilateral lung transplantation for idiopathic pulmonary arterial hypertension with intraoperative venoarterial extracorporeal membrane oxygenation support seems to provide superior outcome compared with the results reported about the use of cardiopulmonary bypass. Prophylactic prolongation of venoarterial extracorporeal membrane oxygenation into the early postoperative period provides stable postoperative conditions and seems to further improve the results.